Posthumanism and the creation of racialised, queer identities and sexualities: An analysis of ‘Steven Universe’ - Roqueta Fernández, Marta (AdMIRA-Análisis de Medios, Imágenes y Relatos Audiovisuales, 2019)
This article analyses how the cartoon show Steven Universe both underpins and defies normative understandings of race, gender and able-bodiedness. By referencing theories from feminist, posthumanist, queer, critical race thinking and crip studies, these concepts are considered technologies whose components can be examined, disassembled and reassembled by the technical object that is the cartoon, which is considered a tool whose meaning is co-established by the audience. By using this conceptual framework to analyse the show’s narrative, as well as to create several surveys that seek to comprehend how people’s notions of gender and race may influence the narrative of the show, the article concludes that Steven Universe creates a queer narrative aimed at dismantling contemporary notions of gender, race and able-bodiedness. However, because the show relies on the components that form these technologies to trouble them, it may fall on stereotypical representations if it overlooks the imaginaries embedded on them.